Examining Trait Anger and Anger Expression Styles of Pro-Licensed Football Coaches - Alparslan Ünveren; Cemal Polat (Türk Spor ve Egzersiz Dergisi)
This study aims to determine the trait anger and anger style levels of football coaches with prolicense in Turkey.The sample group consists of 171 participants selected from within the determined universe by means of easy sampling method.Trait anger and anger expression style scale and personal information form ,developed by Spielberger and colleagues (1983) and Turkish validity and reliability study conducted by Özer(1994) was applied to the sample group.In the scope of the study ,descriptive statistics were used to summarize the demographic characteristics and personal information of the sample group.Data in this study show that there is a significant difference between the groups of the anger control and anger out subdimensions according to the age variable;trait anger and anger out subdimensions according to the educational level; anger control and anger out sub dimensions according to foreign language variable and anger outward subdimensions according to coaching experience.(p lt;0,5). Coaches dealing with football sport encounter multidimensional stimulates in an intense competition environment that will cause anger both in and out of the field.These stimuli affect the emotional worlds and selfies of the coaches positively or negatively.Trait anger and unconrollable external and internal expression style ,as well as legal exposures ,harm the coach’s personality, Professional career and corporate identity.It is thought that the data obtained by this study will shed light on the effects of trait anger ,anger control,anger inward and anger outward situations of football coaches who have the highest degree (pro licence)in our country ;help to develop strategies in anger control and contribute to more research in this field.